Impact of Combustion Variance on Sustainability of Free-Piston Linear Generator during Steady-State Generation - Ahsan Bashir; Saiful A. Zulkifli; Abd Rashid Abd Aziz; Ezrann ZZ Abidin (Energies, 2021)
A free-piston linear generator (FPLG) has a number of advantages compared to a traditional crank-slider internal combustion engine, including better thermal and mechanical efficiencies, different fuel compatibility, and a higher power-to-weight ratio. For electric vehicle propulsion and generation of portable power, an FPLG is a very attractive alternative source of energy. This paper presents the development of an FPLG simulation model using MATLAB-Simulink and investigates the impact of combustion variance on its operation. Results provided insight into various characteristics of system behavior through variation of structural dimension and operational parameters. In steady-state operation with fixed electrical load and fixed ignition for combustion, it was found that consecutively low combustion pressures can easily lead to engine stoppage, pointing to the significance of control for continuous operation. Due to the absence of the moment of inertia and flywheel character of the rotating engine, a linear engine-generator is subject to ceased operation even after two consecutively low combustions under 10% variance. This will not be a fundamental problem in an ordinary crank-slider engine-generator, but in a linear engine-generator, control measure will be necessary to ensure sustained operation.